2018
DOI: 10.26491/mhwm/85507
|View full text |Cite
|
Sign up to set email alerts
|

Is there added value of convection-permitting regional climate model simulations for storms over the German Bight and Northern Germany?

Abstract: Abstract. This study tackles the question: Do very high-resolution convective-permitting regional climate model (RCM) simulations add value compared to coarser RCM runs for certain extreme weather conditions, namely strong wind and storm situations? Ten strong storm cases of the last two decades were selected and dynamically downscaled with the RCM COSMO-CLM (24 and 2.8 km grid point distance). These cyclones crossed the high-resolution model domain, which encompasses the German Bight, Northern Germany, and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The similarity in the long-term evaluation is due to the fact coastDat II was used as forcing data for GB0028. The advantage of the higher resolution is evident in the small-scale synoptic comparison of single weather situations [13]. From all data sets, coastDat II shows the lowest warming (2 m temperature increase of 0.6 • C) occurring for the area mean in the metropolitan region of Hamburg (Figure 1) between the two time intervals 1986-2015 and 1961-1990 (Table 1).…”
Section: Time Slice Comparison Of Gb0028 With Other Data Setsmentioning
confidence: 95%
See 4 more Smart Citations
“…The similarity in the long-term evaluation is due to the fact coastDat II was used as forcing data for GB0028. The advantage of the higher resolution is evident in the small-scale synoptic comparison of single weather situations [13]. From all data sets, coastDat II shows the lowest warming (2 m temperature increase of 0.6 • C) occurring for the area mean in the metropolitan region of Hamburg (Figure 1) between the two time intervals 1986-2015 and 1961-1990 (Table 1).…”
Section: Time Slice Comparison Of Gb0028 With Other Data Setsmentioning
confidence: 95%
“…This is presumably a consequence of the relatively small model domain, as spacious weather patterns which deviate from observed large weather systems have no time to develop inside this domain [31]. The data set was validated regarding added value of this high resolution of 2.8 km compared to a simulation with 24 km grid distance and observations for ten storm events [13]. It was shown that the simulation can reproduce storm events realistically and the added value of the convection-permitting resolution is mainly in synoptic comparisons of single storm cases.…”
Section: Model Configuration and Datamentioning
confidence: 99%
See 3 more Smart Citations